2009
DOI: 10.1136/adc.2009.160366
|View full text |Cite
|
Sign up to set email alerts
|

Is ethnicity a risk factor for severe retinopathy of prematurity?

Abstract: Ethnicity is a risk factor for severe ROP. Asian and black infants have a higher risk of developing threshold ROP compared to white infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…This has been previously noted in Asian Indians37 but the reason for this is unclear. Other differences, for example, rates of HMD and severe IVH were also noted.…”
Section: Discussionmentioning
confidence: 75%
“…This has been previously noted in Asian Indians37 but the reason for this is unclear. Other differences, for example, rates of HMD and severe IVH were also noted.…”
Section: Discussionmentioning
confidence: 75%
“…The reason for the racial differences observed is unclear. Some suggested explanations are (1) a higher rate of small-for-GA infants in Asian populations, (2) genetic variations and (3) pigmentation-related susceptibility to ischaemia-induced retinal vascularisation 21 24. Considering that infants of Korean origin have heavily pigmented fundi, the incidence of severe ROP among these infants, even among the more mature, is worthy of further attention.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies [21, 2832], race and ethnicity have also been identified as significant risk factors, with Whites [30, 32], Asians [31], and Alaskan Natives [28] found to be at increased risk of developing severe ROP. In the present study, we found that race/ethnicity was an independent predictor of any ROP and treatment-requiring ROP.…”
Section: Discussionmentioning
confidence: 99%